On the Security of a Dynamic and Secure Key Management Model for Hierarchical Heterogeneous Sensor Networks - Pengshuai Qiao (Institute of Advanced Engineering and Science, 2014)
With the development of the wireless communication technology and the sensor technology, the wireless sensor network (WSN) has been used in many applications. However, WSNs suffer from some inherent weaknesses because of restricted communication and hardware capabilities. To achieve essentially secure communication in WSNs, a few of key management models have been proposed since it is the crucial important building block for all security goals in WSNs. Recently, Alagheband and Aref proposed a signcryption scheme and used it to construct a dynamic key management model for hierarchical heterogeneous sensor networks. They also proved that their signcryption scheme is provably secure if the elliptic curve discrete logarithm problem is infeasible. Unfortunately, by giving concrete attacks, we indicate that Alagheband and Aref’s signcryption scheme is not secure in their secure model. The analysis also shows that their key management model is not secure. To solve those weaknesses, we also proposed an improved signcryption scheme.